2012
DOI: 10.1016/j.neubiorev.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol dependence as a chronic pain disorder

Abstract: Dysregulation of pain neurocircuitry and neurochemistry has been increasingly recognized as playing a critical role in a diverse spectrum of diseases including migraine, fibromyalgia, depression, and PTSD. Evidence presented here supports the hypothesis that alcohol dependence is among the pathologies arising from aberrant neurobiological substrates of pain. In this review, we explore the possible influence of alcohol analgesia and hyperalgesia in promoting alcohol misuse and dependence. We examine evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
281
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 296 publications
(295 citation statements)
references
References 216 publications
(255 reference statements)
11
281
1
2
Order By: Relevance
“…Alcoholism, or alcohol use disorder, is a complex psychiatric condition characterized by craving, compulsive seeking, and excessive drinking of alcohol, as well as the emergence of negative emotional states during withdrawal (2)(3)(4). Allostatic changes in brain reward and stress systems are thought to mediate many of these symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Alcoholism, or alcohol use disorder, is a complex psychiatric condition characterized by craving, compulsive seeking, and excessive drinking of alcohol, as well as the emergence of negative emotional states during withdrawal (2)(3)(4). Allostatic changes in brain reward and stress systems are thought to mediate many of these symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, a single intense stress or chronic stress produces hyperalgesia (Boccalon et al, 2006; da Silva Torres et al, 2003; Geerse et al, 2006; Quintero et al, 2000; Zhang et al, 2012), increases anxiety-like behaviour, and produces hyperarousal in rats (Campos et al, 2013; Kinn Rød et al, 2012; Serova et al, 2013). Alcohol dependence also promotes hyperarousal and hyperalgesia (i.e., increased nociception), each of which may promote compulsive alcohol drinking (Edwards et al, 2012; Egli et al, 2012; Koob, 1999). Our lab utilizes a predator odor stress model that produces lasting increases in alcohol consumption by rats (Edwards et al, 2013), allowing for the hypothesis that hyperarousal and hyperalgesia may be important motivational factors in stress-induced escalation of alcohol drinking.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that high pain ratings led clinicians to initiate opioid therapy for these participants. Indeed, previous studies demonstrated that patients with SUD are highly sensitive to pain and report greater pain severity relative to those without SUD [45][46][47]. In one scenario, elevated pain ratings in this group of participants prescribed LOT may represent reductions in pain severity from even higher pain ratings observed prior to opioid therapy initiation, albeit to levels still greater than pain ratings endorsed by those not prescribed opioids.…”
Section: Multivariate Model Of Any Prescription Opioid Therapymentioning
confidence: 84%